Full-length transcriptome characterization of Platycladus orientalis based on the PacBio platform - Liao, Ting; Zhang, Linyi; Wang, Ye; Guo, Liqin; Cao, Jun; Liu, Guobin (Frontiers in Genetics, 2024)
As a unique and native conifer in China, Platycladus orientalis is widely used in soil erosion control, garden landscapes, timber, and traditional Chinese medicine. However, due to the lack of reference genome and transcriptome, it is limited to the further molecular mechanism research and gene function mining. To develop a full-length reference transcriptome, tissues from five different parts of P. orientalis and four cone developmental stages were sequenced and analyzed by single-molecule real-time (SMRT) sequencing through the PacBio platform in this study. Overall, 37,111 isoforms were detected by PacBio with an N50 length of 2,317 nt, an average length of 1,999 bp, and the GC content of 41.81%. Meanwhile, 36,120 coding sequences, 5,645 simple sequence repeats (SSRs), 1,201 noncoding RNAs (lncRNAs), and 182 alternative splicing (AS) events with five types were identified using the results obtained from the PacBio transcript isoforms. Furthermore, 1,659 transcription factors (TFs) were detected and belonged to 51 TF families. A total of 35,689 transcripts (96.17%) were annotated through the NCBI nr, KOG, Swiss-Prot and KEGG databases, and 385 transcript isoforms related to 8 types of hormones were identified incorporated into plant hormone signal transduction pathways. The assembly and revelation of the fulllength transcriptome of P. orientalis offer a pioneering insight for future investigations into gene function and genetic breeding within Platycladus species.